Copy number variants and selective sweeps in natural populations of the house mouse (Mus musculus domesticus) - Bryk, Jarosław; Tautz, Diethard (Frontiers in Genetics, 2014)
Copy–number variants (CNVs) may play an important role in early adaptations, potentially facilitating rapid divergence of populations. We describe an approach to study this question by investigating CNVs present in natural populations of mice in the early stages of divergence and their involvement in selective sweeps. We have analysed individuals from two recently diverged natural populations of the house mouse (Mus musculus domesticus) from Germany and France using custom, high–density, comparative genome hybridisation arrays (CGH) that covered almost 164Mb and 2,444 genes. 1,861 of those genes we previously identified as differentially expressed between these populations, while the expression of the remaining genes was invariant. In total, we identified 1,868 CNVs across all 10 samples, 200bp to 600kb in size and affecting 424 genic regions. Roughly two thirds of all CNVs found were deletions. We found no enrichment of CNVs among the differentially expressed genes between the populations compared to the invariant ones, nor any meaningful correlation between CNVs and gene expression changes. Among the CNV genes, we found cellular component gene ontology categories of the synapse overrepresented among all the 2,444 genes tested. To investigate potential adaptive significance of the CNV regions, we selected six that showed large differences in frequency of CNVs between the two populations and analysed variation in at least two microsatellites surrounding the loci in a sample of 46 unrelated animals from the same populations collected in field trappings. We identified two loci with large differences in microsatellite heterozygosity (Sfi1 and Glo1/Dnahc8 regions) and one locus with low variation across the populations (Cmah), thus suggesting that these genomic regions might have recently undergone selective sweeps. Interestingly, the Glo1 CNV has previously been implicated in anxiety–like behaviour in mice, suggesting a differential evolution of a behavioural trait.